2013
DOI: 10.1002/uog.12365
|View full text |Cite
|
Sign up to set email alerts
|

First‐trimester crown–rump length and embryonic volume of aneuploid fetuses measured in virtual reality

Abstract: Objectives To examine whether embryonic volume (EV), as measured using three-dimensional (3D) ultrasound and a virtual reality approach, is a better measure of growth restriction than is crown-rump length (CRL) in aneuploid fetuses. Methods (-27.8%, P < 0.001; -39.4%, P < 0.001; -40.9%, P = 0.004; and -27.3%, P = 0.055, respectively). Conclusions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Furthermore, we performed automatic EV measurement on the same datasets with high success rates. A retrospective study recently showed that EV represents a more effective measurement of first‐trimester growth restriction in aneuploidy fetuses compared with CRL, since all three dimensions are taken into account instead of only one dimension. We minimized confounding of gestational age by including women with strict pregnancy dating only, based on a known LMP, regular cycle and concordant CRL.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we performed automatic EV measurement on the same datasets with high success rates. A retrospective study recently showed that EV represents a more effective measurement of first‐trimester growth restriction in aneuploidy fetuses compared with CRL, since all three dimensions are taken into account instead of only one dimension. We minimized confounding of gestational age by including women with strict pregnancy dating only, based on a known LMP, regular cycle and concordant CRL.…”
Section: Discussionmentioning
confidence: 99%
“…It is not surprising that embryonic growth is related to fetal growth in the second and third trimester of pregnancy and to newborn birthweight (Mook-Kanamori et al 2010;van Uitert et al 2013b). Moreover, when an embryo is relatively small, it has an increased risk of complications during pregnancy, such as fetal chromosomal abnormalities, miscarriage, low birthweight, fetal growth restriction and prematurity (Smith et al 1998;Bukowski et al 2007;Mook-Kanamori et al 2010;Salomon et al 2011;Abuelghar et al 2013;Baken et al 2013;van Uitert et al 2013avan Uitert et al , 2013b. In future, it would be interesting to see whether not only embryonic size, but also embryonic developmental stages are affected by environmental exposures.…”
Section: Dogma Of Uniform Embryonic Growthmentioning
confidence: 99%
“…Animal experiments have shown that IGF-1and IGF-2 are principally involved in fetal growth and placental development, respectively [ 21 , 22 , 23 ]. Fetuses with ES are known to be small for gestational age in the first trimester [ 24 ], and therefore the expression of IGFBP-1 may be altered. Miell et al [ 25 ] was the first to find that maternal serum levels of IGFBP-1 in ES pregnancies were elevated compared to mothers with normal or DS fetuses.…”
Section: Discussionmentioning
confidence: 99%